Copy Write: The Author Survival Guide - Meltzer, Brad (The Columbia Journal of Law & the Arts, 2017)
This is a transcript of the 29th Annual Horace S. Manges Lecture, given by best-selling author Brad Meltzer on March 24, 2016, about his time at Columbia Law School and the importance of doing what you love.